THE INFLUENCE OF TRANSFORMATIONAL LEADERSHIP AND TRANSACTIONAL LEADERSHIP IN CONFLICT MANAGEMENT AT PT POS INDONESIA MAIN BRANCH OFFICE MANADO - Pongoh, Andreas D.; Kindangen, Paulus; Saerang, Regina T. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2019)
Abstract: Human resource becomes one of the very important aspect in the organization in order to be able to mobilize the rest of the resources. In the organization, it is hard to avoid conflict and conflict also might bring damage, to deal with organizational conflict, the leadership role and skill become important to be implemented and good leadership is become the alternative solution. This research aims to analyze the influence of transformational and transactional leadership in conflict management in PT Pos Indonesia Main Branch Office Manado. This research uses quantitative method with questionnaires used to collect the data, and Multiple Linear Regression as the tool of analysis. As the total sample are 47 employees. The result shows that transformational leadership style has a positive relationship and a significant influence toward conflict management also transactional leadership style has a positive relationship and a significant influence toward conflict management at PT Pos Indonesia Main Branch Office Manado. From the results, it is suggested for the company to consider about having an improvement in human resource, with the application of transformational leadership and transactional leadership style in managing conflicts.Â Keywords: transformational leadership, transactional leadership, conflict management